2002
DOI: 10.1021/jp013168v
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Electronic Effects of Ni in Pt/Ni and Pt/Ru/Ni Alloy Nanoparticles in Methanol Electrooxidation

Abstract: Electrooxidation of methanol in sulfuric acid solution was studied using Pt, Pt/Ni(1:1 and 3:1), Pt/Ru/Ni(5: 4:1 and 6:3.5:0.5), and Pt/Ru(1:1) alloy nanoparticle catalysts, in relation to methanol oxidation processes in the direct oxidation methanol fuel cell. The Pt/Ni and Pt/Ru/Ni alloys showed excellent catalytic activities compared to those of pure Pt and Pt/Ru. The role of Ni as a catalytically enhancing agent in the oxidation process was interrogated using cyclic voltammetry, chronoamperometry, X-ray ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
447
3
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 817 publications
(488 citation statements)
references
References 73 publications
28
447
3
3
Order By: Relevance
“…Transition metal oxides have been intensively studied to be widely used in various fields. In addition to its well-known superiority, the other predominant characteristics of transition metal oxides for their groundbreaking application in the ORR should be highlighted: (1) abundant hydroxyl groups are inserted on the surfaces of transition metal oxides, which could be further functionalized by genetic materials (DNA and RNA) for biological catalysts; 11 (2) crystalline construction of transition metal oxides often have strong interactions, which could prevent the agglomeration of metal particles and maintain small metal particle sizes; 12,13 (3) they have considerably higher alkaline corrosion resistance in the electrochemical environment compared to noble metal and carbon-based materials due to the stabilization of the high oxidation state of transition metallic elements. In the past decade, due to excellent nanocomposite catalysts, novel advanced material-based transition metal oxides were created.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal oxides have been intensively studied to be widely used in various fields. In addition to its well-known superiority, the other predominant characteristics of transition metal oxides for their groundbreaking application in the ORR should be highlighted: (1) abundant hydroxyl groups are inserted on the surfaces of transition metal oxides, which could be further functionalized by genetic materials (DNA and RNA) for biological catalysts; 11 (2) crystalline construction of transition metal oxides often have strong interactions, which could prevent the agglomeration of metal particles and maintain small metal particle sizes; 12,13 (3) they have considerably higher alkaline corrosion resistance in the electrochemical environment compared to noble metal and carbon-based materials due to the stabilization of the high oxidation state of transition metallic elements. In the past decade, due to excellent nanocomposite catalysts, novel advanced material-based transition metal oxides were created.…”
Section: Introductionmentioning
confidence: 99%
“…9,25 In our opinion, the good matches between the patterns of the quaternary catalyst and pure Pt crystallites are due the opposite effects that Ru, Ni, and Sn have on the crystal structure. Displacement of the crystallographic planes, indicating alloy formation, have also been observed for some PtRuNi/C electrocatalysts prepared by Park, 10 Wang, 19 Liang, 21 and Moreno 32 via different synthetic routes. Taking into account the XRD pattern, one can infer that the preparation of nanocatalysts by DPP suggest Sn, Ru, and Ni incorporation into the Pt crystallite, with consequent alloy formation.…”
Section: Resultsmentioning
confidence: 62%
“…In addition, materials that have Ni in the presence of Ru and/or Sn have furnished promising results regarding the ethanol oxidation in DEFC. 10,[18][19][20][21] Camara et al 22 has conducted FTIR studies on PtRu and showed that the amount of acetic acid produced is related to the amount of Ru in the catalyst, i.e., the larger the amount of Ru in the electrocatalyst, the higher the formation of acetic acid and the lower the production of acetaldehyde during ethanol oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations